Cellular Therapies in Chronic Granulomatous Disease - Güngör, Tayfun; Chiesa, Robert (Frontiers in Pediatrics, 2020)
Allogeneic hematopoietic stem cell transplantation (HSCT) has become the main curative treatment in patients with chronic granulomatous disease (CGD). CGD is caused by inherited defects of the phagolysomal NADPH-oxidase, leading to a lifelong propensity for invasive infections and granulomatous inflammation. After successful allogeneic HSCT, chronic infections and inflammation resolve and quality-of-life improves. Favorable long-term outcome after HSCT is dependent on the prevention of primary and secondary graft failure (GF), including falling myeloid donor chimerism (DC) below 10 %, and chronic graft-vs.-host-disease (cGVHD). The risk of GF and GvHD increases with the use of HLA-incompatible donors and this may outweigh the benefits of HSCT, mainly in patients with severe co-morbidities and in asymptomatic patients with residual NADPH-oxidase function. Seventeen scientific papers have reported on a total of 386 CGD-patients treated by HSCT with HLA-matched family/sibling (MFD/MSD), 9/10-/10/10-matched-unrelated volunteer (MUD) and cord blood donors. The median OS/EFS-rate of these 17 studies was 91 and 82%, respectively. The median rates of GF, cGVHD and de-novo autoimmune diseases were 14, 10, and 12%, respectively. Results after MFD/MSD and 10/10-MUD-transplants were rather similar, but outcome in adults with significant co-morbidities and after transplants with 9/10 HLA-MUD were less successful, mainly due to increased GF and chronic GVHD. Transplantation protocols using T-cell depleted haploidentical donors with post-transplant cyclophosphamide or TCR-alpha/beta depletion have recently reported promising results. Autologous gene-therapy after lentiviral transduction of HSC achieved OS/EFS-rates of 78/67%, respectively. Careful retrospective and prospective studies are mandatory to ascertain the most effective cellular therapies in patients with CGD.